THE INTERVENING ROLE OF VOLUNTEER SATISFACTION IN ANALYZING THE MOTIVATION OF GENERATION Z TO VOLUNTEER AT THE INDONESIAN RED CROSS OF BANYUWANGI REGENCY: A VOLUNTEER FUNCTIONS INVENTORY MODEL APPROACH - Maimunah, Maimunah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explains volunteer satisfaction as an intervening variable between volunteer motivation and Generation Z's intention to continue volunteering at the Indonesian Red Cross (PMI) Banyuwangi Regency. Referring to the Volunteer Functions Inventory (VFI) model, this study explains six motivational functions, namely value, understanding, social, career, protective, and enhancement. Method: This information was collected from questionnaires and in-depth interviews with 118 Generation Z volunteers. Results: The findings indicated that volunteer motivation had a significant impact on volunteer satisfaction and volunteering intention. Volunteer satisfaction also played the role of a key mediator through which the indirect effect of motivation on volunteering intention was achieved. Novelty: The research highlights the necessity of identifying Generation Z's specific motivation and level of satisfaction in order to devise effective strategies to maintain young volunteers. Practical implications involve the necessity of respective training, appreciating volunteers' efforts, and providing a decent working environment. Conceptual insights into the understanding of volunteer motivation and practical applications that humanitarian organizations can apply to maintain volunteer commitment from your generation are contributed by this study.